"Brown etching layer": A possible new insight into the crack initiation of rolling contact fatigue in rail steels?. (August 2016) - Li, Shaoguang; Wu, Jun; Petrov, Roumen H.; Li, Zili; Dollevoet, Rolf; Sietsma, Jilt
Abstract: A field sample of rail steel was metallurgically examined to characterize its rolling contact fatigue (RCF) damage. In addition to the well-known white etching layer (WEL), a possible different type of surface modification layer was identified in parallel. The layer has some similar features as the WEL but exhibits a significantly different etching response to 3 vol% Nital etchant. After etching, the new layer exhibits a brown color under the same light reflection. This layer was named as "brown etching layer" (BEL) to distinguish it from the WEL. Similar to the WEL, cracks are observed to be closely related to the BEL. The cracks are found to penetrate deeper than those initiated by the WEL reported in existing publications. Further, they are found to propagate downwards without branching, which may eventually cause rail fracture. Although its formation mechanism is not yet clear, WEL has been considered by some authors in the literature as a possible RCF initiation source. It is therefore of critical importance to understand the characteristics of the BEL and its formation mechanism. This may also lead to better understanding of the formation mechanism of the WEL. To this end, microstructural features of the BEL were studied using micro-hardness tests, optical microscopy and scanning electron microscopy. The BEL was found to be distinctly softer than the WEL and lamella-type features are found within the BEL. The microstructural features of the BEL were compared with the WEL reported in the literature. Finally, the formation mechanism of the fatigue damage was discussed based on the comparison, observations and material characterization. Highlights: Brown etching layer (BEL) with low etching resistance and hardness is characterized. Microstructures of BEL and white etching layer (WEL) are shown to be different. Martensite formation mechanism for BEL and WEL is proposed. Plastic deformation contributes to the formation of BEL. A crucial role for BEL in causing fracture is proposed.